RETRACTION:ASSESSMENT OF THE FUNCTIONAL SIGNIFICANCE OF BORDERLINE STENOSIS BY DETERMINING CORONARY FLOW RESERVE, AFTER PRIMARY PERCUTANEOUS INFARCT ARTERY INTERVENTION BY STENT IMPLANTATION (MedPodml 2022, 73(2):59-64) - Vasilev, Vladimir (Medicinski podmladak, 2023)
The Editorial Office of Medical Youth retracts the paper titled “ASSESSMENT OF THE FUNCTIONAL SIGNIFICANCE OF BORDERLINE STENOSIS BY DETERMINING CORONARY FLOW RESERVE, AFTER PRIMARY PERCUTANEOUS INFARCT ARTERY INTERVENTION BY STENT IMPLANTATION” by Irena Čolić, Vladimir Vasilev and Milan Dobrić, published in Volume 73, Issue 2 of Medical Youth. The paper is being retracted in accordance with the author’s request, considering the fact that the paper was published without the autorship of the main contributor of the paper who collected the material used for the research and the writing of the paper. The Editorial Office of Medical Youth hereby expresses great regret and a sincere apology for this type of omission.